Platelet Monoamine Oxidase and Epinephrine-Induced Platelet Aggregation - Rossi, Ennio C; Louis, Gerlinde; Bieber, Martha; Zeller, E Albert (Thrombosis and Haemostasis, 1978)
Platelet MAO activity and the aggregation response to epinephrine, ADP, and collagen were measured in normal subjects. There was a direct correlation between the amount of platelet MAO activity and the per cent aggregation induced by 1 and 2 μM epinephrine. There were lesser correlations between platelet MAO and ADP or collagen-induced aggregation. These findings suggest that platelet MAO may play a role in determining the response of human platelets to epinephrine.